The Influence of Childbirth Procedures to the Axial Length and Sclera Rigidity - Hayati Hayati; Fifin LR; Norma DH (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: Various clinical and experimental studies attest that biochemistry and biomechanical of sclera are factors of influence shape and sclera size which is influence refraction status of the eye. Sclera streatching influenced by intraocular pressure (Valsava maneuver when bearing down effort), extracellular matrix (influenced by estrogene, progesterone and relaxin when pregnant), myopia and age.Objectives: To investigate the influence of delivery procedures of to the axial length and sclera rigidity.Methods: Samples of 60 eyes in two groups; vaginal deliveries (bearing down effort group) and operative deliveries (Caesar group) were tested in the pre and post test control design. Both groups underwent two examinations at prepartum and postpartum including visual acuity, anterior segment, posterior segment, measurement of axial length and sclera rigidity.Results: There were significant differences in the axial length mean in the bearing down effort group; the prepartum axial length is 22.81 ± 0.94 mm and the post-partum is 23.20 ± 0.80 mm. Pre-partum axial length mean is 23.05 ± 1.24 mm and increased to 23.40 ± 1.37 mm in the post-partum samples of Caesar group. This study also found that there were significant differences in the sclera rigidity mean in bearing down effort group which is 0.0144 ± 0.0006 in the prepartum and increase to 0.0163 ± 0.0060 in the postpartum. For the Caesar group, the sclerea rigidity mean was 0.0142 ± 0.0480 in the prepartum and increased to 0.0150 ± 0.0050 in the postpartum. Although no significant effects of bearing down effort to axial length and sclera rigidity was observed, the clinical results indicated that 53,85% of myopia in the bearing down effort groups experienced the increase postpartum corrected-lens approximately between -0,25 D to -0,75D and – 0, 25 D to – 1,00 D in 47,61% of myopia (Caesar groups).Conclusion: There is a significant difference in axial length and sclera rigidity prepartum and postpartum in both groups.